Single-Frontier Bidirectional Search - Moldenhauer, Carsten; Felner, Ariel; Sturtevant, Nathan; Schaeffer, Jonathan (Proceedings of the International Symposium on Combinatorial Search, 2010)
We introduce a new bidirectional search algorithm, Single-Frontier Bidirectional Search (SFBDS). Unlike traditional BDS which keeps two frontiers, SFBDS uses a single frontier. At a particular node we can decide to search from start to goal or from goal to start, choosing the direction with the highest potential for minimizing the total work done. We provide theoretical analysis that explains when SFBDS will work validated by experimental results.